Pivoting to protein: the immunogenicity and safety of protein-based NVX-CoV2373 as a heterologous booster for inactivated and viral vector COVID-19 vaccines - Anthony M. Marchese; Raj Kalkeri; Muruga Vadivale; Nungruthai Suntronwong; Seth Toback; Yong Poovorawan (Taylor & Francis Group, 2023)
Introduction Approximately half of the 13.4 billion COVID-19 vaccine doses administered globally were inactivated or viral vector platforms. The harmonization and optimization of vaccine regimens has become a key focus of policymakers and health-care providers and presents an opportunity to reassess the continued use of pandemic-era vaccines. Areas covered Immunological evidence from studies of various homologous and heterologous regimens has been rapidly published; however, interpretation of these data is complicated by the many vaccine types and highly variable participant viral exposure and vaccination histories. Recent studies demonstrate that after primary series doses of inactivated (i.e. BBV152, and BBIBP-CorV), and viral vector (ChAdOx1 nCov-2019) vaccines, a heterologous boost with protein-based NVX-CoV2373 elicits more potent ancestral strain and omicron-specific antibody responses compared to homologous and heterologous inactivated and viral vector boosts. Expert opinion While mRNA vaccines likely yield similar performance to protein-based heterologous booster doses, the latter offers notable advantages to countries with high uptake of inactivated and viral vector vaccines in terms of transportation and storage logistics and can potentially appeal to vaccine hesitant individuals. Moving forward, vaccine-mediated protection in inactivated and viral vector recipients may be optimized with the use of a heterologous protein-based booster such as NVX-CoV2373. Pivoting to Protein The Immunogenicity and Safety of Protein-based NVX-CoV2373 as a Heterologous Booster for Inactivated and Viral Vector COVID-19 Vaccines. Inactivated or viral vector primary series following a booster dose with homologous or heterologous inactivated vaccines (i.e., BBV152, BBIBP-CorV), and homologous or heterologous viral vector vaccines (i.e., ChAd-Ox1 nCov-19) induces suboptimal immunogenicity compared to the enhanced immunogenicity of heterologous protein-based vaccine NVX-CoV2373.